Efektivitas Metode Praktikum Larutan Elektrolit Dan Non Elektrolit Berbasis Inkuiri Terbimbig Terhadap Hasil Belajar Siswa - Kristina Aidies Adelia; Aceng Haetami; Haeruddin (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2023)
This research was conducted with the aim of determining student activities in the application of guided inquiry-based practicum methods on electrolyte and non-electrolyte solution materials, knowing the effectiveness of applying guided inquiry-based practicum methods on student learning outcomes on electrolyte and non-electrolyte solution materials and knowing student responses in the application of guided inquiry-based practicum methods on electrolyte and non-electrolyte solution materials. The sample in this study was 26 students of class X. The research method used is Pre Experiment with One-group Pre-test Post-test Design research design. Data collection in this study used research instruments in the form of multiple-choice questions totaling 20 questions, observation sheets of student and teacher activities, and questionnaires of student responses to the learning process. The results of the study were obtained: The average student learning outcomes increased after being taught using the guided inquiry learning model, namely 86.92,the average percentage of student activity and teaching teachers during 2 meetings was 77% with excellent categories and 81% with excellent categories and students' response to the guided inquiry learning model was relatively good with a percentage of 74.37%.